Pengaruh Pendapatan dan Pola Konsumsi Pemulung Terhadap Prilaku Menabung (Studi Kasus Pemulung Kampung Legok Kota Jambi) - Subhan Subhan (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2018)
This paper aims to reveal (1) to find out the average monthly income of scavengers in 2016 (2) to determine the average monthly consumption of scavengers in 2016 (3) to see if there is a relationship between the level of income and consumption of scavengers on the saving behavior of scavengers. This research is a field research with a population of people or scavengers in Kampung Legok, Jambi City. The technique of sampling is the Slovin technique. The number of samples in this study were 34 scavengers. The data collection technique used was a questionnaire. The average monthly income of scavengers in Kampung Legok, Jambi City is Rp. 1,325,000, while the highest monthly income is Rp. 1,650,000, then the lowest monthly income is Rp. 980,000 and the overall income of scavengers in Legok Village, Jambi City is Rp. 45,050,000. The average consumption of scavengers in Kampung Legok, Jambi City per month is Rp. 1,277,000, while the highest monthly income is Rp. 1,500,000, then the lowest income is Rp. 10,300,000 and the overall income of scavengers in Kampung Legok, Jambi City is Rp. 43,420,000. The level of income and consumption of scavengers is known after a correlation test is carried out that the income is 1,000 and the consumption is 5.86 with a significant number of 0,000, so there is no significant relationship between the level of income and consumption of scavengers with the saving behavior of scavengers in Kampung Legok, Jambi City.